Elemen Arsitektur Pembentuk Karakter Bangunan pada Tapak Warisan Dunia Kota Sawahlunto Sumatera Barat, Indonesia - Rika Cheris; Imbardi Imbardi; Lalu Muhammad Ivan (ARSITEKTURA, 2021)
The mining industrial city of Sawahlunto has been designated as a World Heritage Site recognized by UNESCO in 2019. The designation of this building has been through a study of its form, function, ownership and area. However, urban development will still occur. This is of course caused by several factors. Changes in the city, the design and function of these buildings need to be controlled to keep cultural heritage buildings from being lost. For this reason, research is needed to determine the character-forming elements of cultural heritage buildings in Sawahlunto City. This will be very useful for the Government to make guidelines for the restoration of cultural heritage buildings. The research method used is qualitative descriptive analysis with the UNESCO attribute building sample method that will be selected in each area. For this initial stage, the sample to be taken is in the core area (Map of Land Ownership Area A, Sawahlunto Mining and company town: A5 company town, Nominated Property) in the Ombilin Sawahlunto mining world heritage site, West Sumatra. The sample will become a guideline for similar buildings, then will become a reference for any conservation